Comparison of depressive symptoms and anxious distress between major depressive disorder and bipolar disorder using the CUDOS‐A - Kazufumi Oishi; Yasuyuki Matsumoto; Yumi Aoki; Yoshikazu Takaesu; Masami Murao; Taku Maruki; Takashi Tsuboi; Masahiro Nakano; Koichiro Watanabe; Hitoshi Sakurai (Psychiatry and Clinical Neurosciences Reports, 2026)
Abstract Aim Anxious distress is a clinically important specifier associated with adverse outcomes in mood disorders. This study aimed to compare the prevalence of anxious distress and overall depressive symptoms between patients with major depressive disorder (MDD) and bipolar disorder (BD) using validated self‐report measures. Methods This cross‐sectional study included 202 psychiatric outpatients (133 MDD and 69 BD) recruited from seven outpatient clinics in Japan. Participants completed the Clinically Useful Depression Outcome Scale supplemented with the DSM‐5 anxious distress specifier (CUDOS‐A) and the Quick Inventory of Depressive Symptomatology, Self Report (QIDS‐SR). Anxious distress was operationally defined using the CUDOS‐A items corresponding to the DSM‐5 anxious distress specifier. Group differences in prevalence and mean scores were examined using chi‐square tests and independent samples t ‐tests, respectively. Results The prevalence of anxious distress was 42.9% in patients with MDD and 43.4% in those with BD, with no significant difference between groups ( p = 0.95). No significant differences were observed in the mean CUDOS‐A total scores (28.0 ± 19.9 vs. 27.0 ± 17.7, p = 0.57) or the QIDS‐SR total scores (13.6 ± 7.6 vs. 12.1 ± 7.4, p = 0.18). Furthermore, all individual items of the CUDOS‐A showed no significant differences between the two groups. Conclusions Both anxious distress and overall depressive symptom severity assessed by self‐report measures appear to be comparable between MDD and BD. Although the diagnostic utility of anxious distress for differentiating between the two disorders has not been established, its high prevalence in both groups underscores its clinical significance and supports the need for routine assessment in mood disorders.